Assessing Span Between Feet of Squatting-Type Toilet for Childhood Based on Antropometric Data in Pos PAUD Aqila Kids Desa Rimbo Panjang - Resy Kumala Sari; Sri Hardianti; Sumianto Sumianto; Nurul Dwi Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2022)
The use of toilets in Indonesia mostly uses the squat toilet type. The squat toilet is a type of toilet that is comfortable and stable in its use. The type of squat toilet in Indonesia, especially in Riau, has the most widely used toilet for adults, this is very difficult for young children in a smaller time span than adults so that children are not comfortable and stable when using a squat toilet. The service method was carried out at the Aqila Kids PAUD Post in Rimbo Panjang Village, and was attended by 15 students along with parental assistance. The result of this socialization is that it can increase knowledge about the distance between children's feet by measuring the distance between the legs when children squat, education on the importance of using squat toilets from an early age and knowledge in using squatting toilet training. The empowerment of teachers and parents in monitoring the use of squatting toilet training is expected to be realized properly by presenting several examples of squatting properly and correctly so as to create a comfortable and safe atmosphere.